Opening a window to the West : the foreign concession at Kobe, Japan, 1868-1899 - Ennals, Peter (Japan and global society., 2014)
The first book-length study of Kōbe's Foreign Concession, Opening a Window to the West situates Kōbe within the larger pattern of globalization occurring throughout East Asia in the nineteenth century.